The development of a Geographic information system for environmental monitoring on the Cape Peninsula, and an assessment of the use of spot imagery for vegetation mapping - Webster, Michael S (Department of Biological Sciences, 2016)
This thesis concerns the establishment of a Geographic Information System for the Cape Peninsula and the use of SPOT satellite imagery to map land cover classes. The former is seen as a necessary tool to promote judicious conservation management decisions for the fragile "Fynbos" ecosystem, and the latter as a convenient means of acquiring up-to-date information concerning the environment, and to monitor change.